Melatonin regulates oxidative stress and apoptosis in fetal hearts of pinealectomised RUPP rats - Oğuzhan Doğanlar; Zeynep Banu Doğanlar; Mehmet Akif Ovali; Orkut Güçlü; Ufuk Demir; Ayten Doğan; Metehan Uzun (Taylor & Francis Group, 2020)
Objective: This study aimed to investigate the effects of melatonin on cardiac oxidative stress and apoptosis in the fetal heart in RUPP rats. Methods: The fetal heart samples were obtained from melatonin administrated RUPP rats Results: Our results indicate that preeclampsia exacerbated by melatonin deficiency triggers hypoxic conditions, both mis/un-folded protein response, oxidative stress-induced DNA damage and apoptosis. Melatonin treatment provided significant therapeutic effects on fetal hearts via regulating all these stress response at cellular and molecular levels. Conclusion: Melatonin may be considered as a potential molecule for development of preventive strategies to reduce the PE induced risk of cardiovascular diseases in offspring.